Engaging mixed methodology to Gauge Industrial Relations Quality Determinants / Elizabeth Caroline Augustine, Nur Aida Kipli and Kuldip Singh - Augustine, Elizabeth Caroline; Kipli, Nur Aida; Singh, Kuldip (Universiti Teknologi MARA, Sarawak, 2023)
Several scholars have claimed that harmonious and quality industrial relations lead to organizational development. There are studies and instruments to measure industrial relations harmony. However, so far, document searches based on SCOPUS and Google Scholar databases revealed a lack of evidence based on empirical studies conducted on industrial relations quality and measurements used to determine the quality of industrial relations. This paper attempts to discuss how industrial relations quality determinants are gauged employing a mixed methodology approach. The quality of industrial relations in East Malaysia would be assessed. Data collection for both approaches was conducted online due to the COVID-19 movement control order. NVivo 12 plus was used to explore and identify industrial relations best practices. The Statistical Package for Social Sciences (SPSS) version 26 was used to gauge industrial relations quality determinants and determine the quality of industrial relations. There were seven industrial relations practices identified.